2011
DOI: 10.1007/s00402-011-1278-5
|View full text |Cite
|
Sign up to set email alerts
|

Valgus intertrochanteric osteotomy for coxa vara of Bucholz–Ogden Types II and III in patients older than 30 years

Abstract: Based on results, the valgus intertrochanteric osteotomy appears to be a reliable treatment for postdysplastic coxa vara in patients older than 30 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…The great advantages of the intertrochanteric osteotomy over the subtrochanteric osteotomy include that it is done in the metaphyseal highly cancellous proximal femoral bone with high power of union, which is nearer to the site of the hip deformity with easier deformity correction and also it obviates radiologic disadvantage of a subtrochanteric osteotomy, which is the creation of a secondary angular deformity in the form of femoral shaft kinking distal to the primary deformity. 7 8 14 16 17) On the other hand the authors reported that this radiological kinking remodels significantly and has no negative influence on hip function. 4) In the present study, the length of the oblique limb of the Y-shaped osteotomy was fixed to be one-half of the diameter of the femur at the level of the osteotomy.…”
Section: Discussionmentioning
confidence: 95%
“…The great advantages of the intertrochanteric osteotomy over the subtrochanteric osteotomy include that it is done in the metaphyseal highly cancellous proximal femoral bone with high power of union, which is nearer to the site of the hip deformity with easier deformity correction and also it obviates radiologic disadvantage of a subtrochanteric osteotomy, which is the creation of a secondary angular deformity in the form of femoral shaft kinking distal to the primary deformity. 7 8 14 16 17) On the other hand the authors reported that this radiological kinking remodels significantly and has no negative influence on hip function. 4) In the present study, the length of the oblique limb of the Y-shaped osteotomy was fixed to be one-half of the diameter of the femur at the level of the osteotomy.…”
Section: Discussionmentioning
confidence: 95%
“…Various hip preservation surgeries used to be performed for the young patients with hip dysplasia or ONFH [2, [14][15][16]. When these patients developed arthritis, the residual deformity would bring more challenge to the following THA [17].…”
Section: Discussionmentioning
confidence: 99%
“…In the past, various hip-preserving surgeries were performed for the young patients with hip dysplasia or ONFH [2,[10][11][12]. When these patients developed arthritis, the residual deformity would bring more challenge to the following THA [13].…”
Section: Discussionmentioning
confidence: 99%